Hubungan Dukungan Sosial dengan Kepercayaan Diri Siswa Pada Mata Pelajaran IPA di SMP Negeri 13 Tanjungpinang - Putri, Riri Indriana; Fernando, Adam; Amelia, Trisna (Symbiotic: Journal of Biological Education and Science, 2025)
Adequate social support encouraged students to trust their abilities more and participate actively in learning. The purpose of this study was to determine the relationship between social support and students' self-confidence in science subjects at SMP Negeri 13 Tanjungpinang. This correlational research involved 103 students from grades VII and VIII as the population, with the total sampling technique employed for sample selection. Data were collected through questionnaires using valid and reliable closed-ended instruments, with Cronbach’s alpha reliability coefficients of 0.933 for the social support questionnaire and 0.894 for the self-confidence questionnaire. Data analysis techniques included descriptive statistical analysis, the product moment correlation test, and the t-test to examine the significance of the relationship between the two variables. The research results indicated a significant positive relationship between social support and students' self-confidence in science subjects at SMP Negeri 13 Tanjungpinang. The instrumental support aspect, such as material assistance and learning facilities, was most dominantly perceived by students. This assistance made students feel valued, thereby enhancing their spiritual confidence. Feelings of gratitude strengthened the belief that God provided pathways for continuous learning through the people around them. These findings affirmed the importance of social support in enhancing students' self-confidence in learning.